Psychoeducational of Healthy Dating to Reduce the Risk of Sexual Violence in Female Street Children - Sri Kushartati, Dessy Pranungsari, Koentjoro (Universitas Ahmad Dahlan, 2014)
Abstract This study was conducted to determine whether psychoeducational of healthy dating can reduce the risk of sexual violence in female adolescents of street children community. Subjects in this study were 8 adolescents of street children community of North Square of Yogyakarta. The study design used one group pretest-posttest design and follow up. The results of Wilcoxon test showed no significant difference between the scores of sexual violence before psychoeducational healthy dating (pretest) and after (post-test) with Z = -1.420 and p = 0.156 (p> 0.05), the mean of decrease in score was 4.44. Likewise, there was no difference between the scores of sexual assault after courting healthy psychoeducational (posttest) and during follow-up with z = -1.612 and p = 0.107 (p> 0.05), the mean decrease in score was 4. However, there were significant differences between the scores of sexual violence before (pretest) and follow-up with z = -2.103 and p = 0.035 (p <0.05), the mean of decrease in score was 8.44 which indicated that the application of a healthy dating psychoeducational could reduce the risk of sex violence on girls in street children community, but it needed 1 month to be applied in the form of healthy dating behavior. Keywords: psychoeducational of healthy dating, sexual violence, street children.